Infotech@Aerospace 2011 2011
DOI: 10.2514/6.2011-1451
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Backstepping Design for a Longitudinal UAV Model Utilizing a Fully Tuned Growing Radial Basis Function Network

Abstract: Classical Radial Basis Function (RBF) neural network controller designs typically fix the number of basis functions and tune only the weights. In this paper we present a backstepping neural network controller algorithm in which all RBF parameters, including centers, variances and weight matrices are tuned online. By using a Lyapunov approach, tuning rules for updating the RBF parameters are derived and a stability and robustness analysis is presented. Additionally, we incorporate the ability to append RBF neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The 6-DOF nonlinear model of UCAV is illustrated in this section, which is the prerequisite for simplifying and linearizing the mathematical model (Lombaerts, 2012;Luo et al, 2011;Zhang and Duan, 2013). Figure 1 gives some information about the coordinate system of the aircraft.…”
Section: Mathematical Model Of Ucavmentioning
confidence: 99%
“…The 6-DOF nonlinear model of UCAV is illustrated in this section, which is the prerequisite for simplifying and linearizing the mathematical model (Lombaerts, 2012;Luo et al, 2011;Zhang and Duan, 2013). Figure 1 gives some information about the coordinate system of the aircraft.…”
Section: Mathematical Model Of Ucavmentioning
confidence: 99%
“…These factors will greatly increase the instability of the system. To compensate for the disturbance caused by the external uncertainty, radial basis function NN (RBFNN) is broadly adopted as disturbance compensator and auxiliary controller on account of its strong non‐linear mapping ability [6, 23]. Lai et al [22] focus on the application of rotorcraft to autonomously load carrying and transport.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that under PID control, a helicopter UAV will successfully reject added load offsets within a fairly large range, but the external interference was not considered. In [23], an adaptive controller based on a fully tuned growing RBFNN was designed to realise auto landing sequence for an UAV. For the existing design tools, on the one hand, non‐linearity and coupling are often approximated or even neglected for the sake of simplifying system model which may not accurately measure the input and output characteristics of the system, on the other hand, some complex controllers are designed to suppress unknown non‐linear disturbances that directly increase the load of calculation.…”
Section: Introductionmentioning
confidence: 99%